Antifungal Activity and Potential Mechanism of N-Butylphthalide Alone and in Combination With Fluconazole Against Candida albicans - Gong, Ying; Liu, Weiguo; Huang, Xin; Hao, Lina; Li, Yiman; Sun, Shujuan (Frontiers in Microbiology, 2019)
Candida albicans is a common opportunistic fungal pathogen that may cause nosocomial fungal infections. The resistance of Candida albicans to traditional antifungal drugs has been increasing rapidly in recent years and it brings a great challenge in clinical treatment. N-butylphthalide is originally extracted from the seeds of Apium graveolens and currently used for the treatment of ischemic stroke in clinic. This study demonstrated that n-butylphthalide exhibited antifungal activity against Candida albicans with minimum inhibitory concentrations of 128μg/mL and n-butylphthalide combined with fluconazole showed synergistic antifungal effects against resistant Candida albicans, resulting in a decrease in the minimum inhibitory concentrations of fluconazole from >512 to 0.25-1μg/mL. Time-killing curves verified the antifungal activity in dynamic. Besides, n-butylphthalide exhibited anti-biofilm activity against Candida albicans biofilms preformed <12h with sessile minimum inhibitory concentrations of 128-256μg/mL and synergism was observed when n-butylphthalide combined with fluconazole against resistant Candida albicans biofilms preformed <12h, resulting in a decrease in the sessile minimum inhibitory concentrations of fluconazole from >1024 to 0.5-8μg/mL. Furthermore, in vitro antifungal effects of n-butylphthalide were confirmed in vivo. N-butylphthalide prolonged survival rate of larvae infected by Candida albicans, reduced the fungal burden in larvae and caused less damage to larval tissues. Notably, n-butylphthalide inhibited hyphal growth and induced intracellular reactive oxygen species accumulation and a loss in mitochondrial membrane potential, which were potential antifungal mechanism. Besides, the synergistic effects between n-butylphthalide and fluconazole potentially relied on the mechanism that n-butylphthalide significantly promoted drug uptake, suppressed drug efflux and then increased intracellular concentrations of fluconazole.